Bisphenols A, F, S and AF trigger apoptosis and/or endoplasmic reticulum stress in human endometrial stromal cells. (August 2022) - Ferreira, Ricardo; Amaral, Cristina; Correia-da-Silva, Georgina; Almada, Marta; Borges, Margarida; Cunha, Sara Cristina; Fernandes, José Oliveira; Teixeira, Natércia
Abstract: Disruption of non-differentiated endometrial stromal cells could have noxious consequences in female reproduction, impairing endometrial remodelling and implantation. Following the classification of bisphenol A (BPA) as an endocrine disrupting chemical, it started to be gradually withdrawn from the market, being substituted by structural analogues, whose effects in human health are not fully understood. This work used a telomerase-immortalized human endometrial stromal cell line (St-T1b) to study the effects of BPA and its three most commercialized structural analogues (ranked: bisphenols S, F and AF) on endometrial stromal cells to understand their effects on female reproductive function. Bisphenols showed dissimilar effects. All four compounds generated endoplasmic reticulum (ER) stress. In addition, bisphenols A, F and AF induced apoptosis through different mechanisms, with bisphenol AF causing cell cycle arrest at G2 /M phase. Bisphenol AF decreased mitochondrial transmembrane potential and bisphenols A, F and AF produced oxidative stress. Highlights: Bisphenols A, F and AF induce apoptosis in endometrial stromal cells. Bisphenols A, F, S and AF induce ER-stress in endometrial stromal cells. Bisphenols AF and S were, respectively, the most and least toxic compounds.